Effect of Freshwater and Seawater Immersion on Mechanical Properties and Pre-Immersion Magnetic Response of Silicone Rubber–Magnetite Composite Magnets - Wibowo Wibowo; Nehemia Herbert Santoso; Brilliano Wahyu Ramadhan; Wibawa Endra Juwana; Mujtahid Kaavessina (Jurnal Ilmu Fisika, 2026)
Magnetite (Fe₃O₄) and RTV 48 silicone rubber-based magnetic composites have potential for outdoor applications due to their flexible and tunable magnetic properties. This study investigates the effect of immersion for 14 days in fresh water and seawater on its mechanical, magnetic, and thermal properties. Specimens were made by mixing 70 wt% Fe₃O₄ powder into RTV 48 matrix, then tested for hardness using Shore A durometer, magnetic properties using Vibrating Sample Magnetometer (VSM), and thermal stability using Thermogravimetric Analysis (TGA). Results showed a decrease in surface hardness due to matrix degradation by water penetration. The magnetic properties continued to exhibit soft magnetic characteristics with low coercivity and remanence. TGA analysis revealed changes in thermal degradation patterns, signaling chemical interactions between the material and the wet environment. These findings suggest that exposure to water can affect the long-term performance of Fe₃O₄-RTV 48 composites, making moisture resistance an important aspect for their outdoor applications.